Development of an automated robot vision component handling system - Jansen van Nieuwenhuizen, Rudolph Johannes (Bloemfontein : Central University of Technology, Free State, 2013)
In the industry, automation is used to optimize production, improve product quality and increase profitability. By properly implementing automation systems, the risk of injury to workers can be minimized. Robots are used in many low-level tasks to perform repetitive, undesirable or dangerous work. Robots can perform a task with higher precision and accuracy to lower errors and waste of material. Machine Vision makes use of cameras, lighting and software to do visual inspections that a human would normally do. Machine Vision is useful in application where repeatability, high speed and accuracy are important. This study concentrates on the development of a dedicated robot vision system to automatically place components exiting from a conveyor system onto Automatic Guided Vehicles (AGV). A personal computer (PC) controls the automated system. Software modules were developed to do image processing for the Machine Vision system as well as software to control a Cartesian robot. These modules were integrated to work in a real-time system. The vision system is used to determine the parts‟ position and orientation. The orientation data are used to rotate a gripper and the position data are used by the Cartesian robot to position the gripper over the part. Hardware for the control of the gripper, pneumatics and safety systems were developed. The automated system‟s hardware was integrated by the use of the different communication protocols, namely DeviceNet (Cartesian robot), RS-232 (gripper) and Firewire (camera).
Thesis (M. Tech. (Engineering: Electrical)) -- Central University of technology, Free State, 2013
Keywords: Central University of Technology, Free State - Dissertations; Automated guided vehicle systems; Robot vision; Robot vision - Control; Assembly-line methods; Flexible manufacturing systems; Dissertations, Academic - South Africa - Bloemfontein